Successful Learners' Learning Strategies At The English Department - Lalu Isnaeni Rahman; Fachrurrazy Fachrurrazy; Arwijati Wahyudi (Universitas Negeri Malang, 2015)
Abstract: This research was intended to find out learners' learning strategies at the English Department of STKIP PGRI Blitar. The case study method was used to conduct the research about particular learners. Subjects were selected according to their score (GPA). Data were collected through note taking and interviewing. The researcher selected, simplified and organized the raw data which refer to the research problem being investigated, then data were displayed carefully. Findings show that successful learners employ different learning strategies. The basic key of success that can be drawn is that the more strategies the learners employ the more open the possibilities for success become. Key Words: language learning strategies, successful learner   Abstrak: Penelitian ini bertujuan untuk mengetahui strategi belajar peserta didik Jurusan Bahasa Inggris STKIP PGRI Blitar. Metode studi kasus digunakan untuk melakukan penelitian tentang peserta didik tertentu. Subjek dipilih sesuai dengan nilai mereka (IPK). Data dikumpulkan melalui taking note dan wawancara. Peneliti memilah, menyederhanakan dan mengorganisir data mentah yang mengacu pada masalah penelitian yang diteliti, lalu data ditampilkan dengan hati-hati. Temuan menunjukkan bahwa peserta didik yang sukses adalah mereka yang menerapkan teknik strategi belajar yang berbeda. Kunci dasar keberhasilan yang dapat ditarik adalah bahwa semakin banyak strategi belajar yang di-gunakan kesempatan sukses akan menjadi lebih terbuka. Kata kunci: strategi pembelajaran bahasa, pelajar yang sukses